Model Matematik Prediksi Pembentukan Biogas dari Limbah Kotoran Ternak - Putra, Guyup Mahardhian Dwi; Setiawati, Diah Ajeng (LPPM Universitas Mataram, 2024)
Petroleum is currently the most commonly used fuel in Indonesia, but its availability is decreasing! Therefore, alternative energy sources are needed.Â One solution is to convert agricultural and livestock waste into biogas, which is a renewable and environmentally friendly energy source! Biogas can be used for cooking, generating electricity, and even as fuel for vehicles! The aim of this research is to develop a mathematical model for predicting biogas volume! Can you believe it? The experiment involved creating biogas from a mixture of cow dung and water in a 1:2 ratio. The mixture was stirred until evenly distributed in a portable biogas floating drum. No gas was formed from the first day until the seventh day, but on the eighth day, gas began to form and its volume was recorded! A mathematical model approach, namely the Gompertz and Logistic Models, was used to predict the formation of biogas volume! And guess what? The results indicate that both models were able to predict the data accurately with a coefficient of determination (R2) of 0.99!Â The validity test results show that the Gompertz model is the most reliable for making predictions! This is indicated by the bias value of 0.002, MSEP value of 0.000, and EI of 0.058. The validity test value is smaller than the validity test value obtained in the Logistic model, which is a bias value of 0.016, MSEP value of 0.005, and Ei value of 0.329.